The paper of the professionals and family in the Visual Disability from the theoretical review - Prado, Jose Enrique Llamazares de; Gago, Ana Rosa Arias; Alvarez, Maria Antonia Melcon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
There are few studies dealing with the relationship between the family, disability, and health and education professionals. He present work has as main objective it review of them studies on the role of families of people with functional diversity and its relationship with the professionals involved. We want a systematic reflection of the synthetic quantitative estimate of all of the available studies, establishing a theoretical framework on the situation of the families of people with functional diversity and its relationship with health and education professionals. In this study provides personal estimations about the above mentioned variables. Within them conclusions obtained, is evidence the relevance of the cooperation joint of family and professional for an education effective, with an involvement more significant from the parents in the school.